Reduced 3D-left atrium ejection fraction predicts development of atrial fibrillation in patients with hypertrophic cardiomyopathy. (3rd October 2022) - Amador, A; Martins Da Costa, C; Calvao, J; Pinto, R; Proenca, T; Carvalho, J M; Cabrita, A; Marques, C; Pinho, A; Santos, L; Oliveira, C; Moreira, H; et al.
Abstract: Introduction: Atrial fibrillation (AF) is the most common sustained arrhythmia in hypertrophic cardiomyopathy (HCM), occurring in approximately 25% of patients, related to left atrial (LA) dilatation and remodeling. HCM patients who develop AF have increased risk of HCM-related death, functional impairment, and stroke. Accurate risk stratification for AF in this population is crucial as contemporary treatments are highly successful. Purpose: To assess if new echocardiographic parameters can predict the development of AF in HCM patients. Methods: HCM patients who underwent comprehensive echocardiographic examination during 2011 were followed and checked for "de novo" AF until November 2021. We searched for associations between AF development and novel echocardiographic parameters such as LA Volume index, Left Atrioventricular Coupling Index (LACI, as LAVI/a'), 3D LA volumes and 3D LA ejection fraction (3D-LAEF). Results: A total of 43 patients were included, with 62.8% male and mean age 56, 1±6, 2 years old. 55.8% had the septal asymmetric HCM type and mean LV mass was 326±127g. Mean LA diameter and biplane 2D volume was 46±7 mm and 78±37 mL, respectively. 11.6% of patients already had AF. During a median follow-up of 9.4 years, the incidence of "de novo" AF was 31, 6%. Within the total 17 patients with AF, 35, 2% took warfarin and the remaining direct oral anti-coagulation. No stroke was documented. There were 3 deaths (mortality rate of 7, 0%), none from cardiac causes. No association was found between AF development and LAVI, LACI or 3D LA volumes. We only found a statistically significant difference regarding 3D-LAEF, which was lower in patients who developed AF compared with those without AF (26±12% VS 39±19%, p=0.04). Binary logistic regression analysis found that reduced 3D-LAEF predicts the development of AF (p=0.019, odds ratio [OR] 2.6, 95% confidence interval [CI] 1.0 to 1.1). The area under a receiver operating characteristic curve using 3D-LAEF as a predictive marker for AF development in HCM patients was 0.743 (p=0.004). When the cut-off value of 3D-LAEF was set at 34, 5%, the sensitivity and specificity for AF diagnosis were 66% and 86%, respectively. Conclusion: In our study, 3D LAEF predicted the development of AF in HCM patients – this may be a useful tool to identify patients at high risk of future AF who may benefit from more intensive rhythm monitoring and a lower threshold for oral anticoagulation. Funding Acknowledgement: Type of funding sources: None.